Antidotes to coumarins, isoniazid, methotrexate and thyroxine, toxins that work via metabolic processes. (24th October 2015) - Bateman, D. Nicholas; Page, Colin B.
Abstract : Some toxins cause their effects by affecting physiological processes that are fundamental to cell function or cause systemic effects as a result of cellular interaction. This review focuses on four examples, coumarin anticoagulants, isoniazid, methotrexate and thyroxine from the context of management of overdose as seen in acute general hospitals. The current basic clinical pharmacology of the toxin, the clinical features in overdose and evidence base for specific antidotes are discussed. The treatment for this group is based on an understanding of the toxic mechanism, but studies to determine the optimum dose of antidote are still required in all these toxins except thyroxine, where treatment dose is based on symptoms resulting from the overdose.